Human Cytomegalovirus-Induced Interleukin-10 Production Promotes the Proliferation of Mycobacterium massiliense in Macrophages - Quan, Hailian; Kim, Jiyeon; Na, Yi Rang; Kim, Jung Heon; Kim, Byoung-Jun; Kim, Bum-Joon; Hong, Jung Joo; Hwang, Eung Soo; Seok, Seung Hyeok (Frontiers in Immunology, 2020)
Human cytomegalovirus (HCMV) exploits the interleukin-10 (IL-10) pathway as a part of its infection cycle through the manipulation of the host IL-10 signaling cascade. Based on its immunomodulatory nature, HCMV attenuates the host immune response and facilitates the progression of co-infection with other pathogens in an immune-competent host. To investigate the impact of HCMV infection on the burden of nontuberculous mycobacteria (NTM), whose prevalence is growing rapidly worldwide, macrophages were infected with HCMV and further challenged with Mycobacterium massiliense (M. mass) in vitro. The results showed that HCMV infection significantly increased host IL-10 synthesis and promoted the proliferation of M. mass in an IL-10-dependent manner. Transcriptomic analysis revealed that HCMV infection dampened the regulatory pathways of interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), and interleukin-1 (IL-1), consequently abrogating the immune responses to M. mass coinfection in macrophages. These findings provide a mechanistic basis of how HCMV infection may facilitate the development of pathogenic NTM co-infection by upregulating IL-10 expression.